Composite positive electrode material and preparation method and application thereof
By using a double cladding of disordered phase and nano lithium iron phosphate material on the surface of the high nickel positive electrode material, the rapid attenuation of capacity and cycle retention rate of high nickel positive electrode material during charge storage and cycle, achieving longer cycle life and better battery performance.
Patent Information
- Application Number
- CN202411684674.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing high-nickel positive electrode materials are susceptible to electrolyte during charge storage, resulting in rapid attenuation of capacity; the particles are broken due to volume changes during the cycle, and the cycle retention rate is rapidly attenuated.
The composite positive electrode material is used, and the core matrix includes nickel-cobalt lithium manganate material. The surface is double coated with disordered phase material and nano-lithium iron phosphate material to form film-like and dot-like cladding layers to enhance the protection of the material.
Through the protection of the double cladding, the cycle life and charge storage life of the core matrix material are extended, and the cycle performance and safety performance of the battery are improved.
Smart Images

Figure CN119581518A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a composite positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density and good cycle performance, and are widely used in electronic products, automobiles, aerospace and other fields. As people's requirements for the environmental protection, battery life and life of lithium-ion batteries gradually increase, the optimal design of batteries is becoming more and more important. As the core of lithium-ion batteries, the quality of positive electrode materials directly determines the performance of batteries. The defects of existing high-nickel positive electrode materials include: due to insufficient surface interface protection, the capacity often decays rapidly due to electrolyte erosion during charged storage; during cycling, the volume change during the charge and discharge process causes particle breakage, resulting in a rapid decay of the cycle retention rate.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] One object of the present invention is to provide a composite positive electrode material to solve the technical problem that the capacity and cycle retention rate of existing high-nickel positive electrode materials decay quickly.
[0005] Another object of the present invention is to provide a method for preparing the composite positive electrode material, which is simple and easy to implement, and the obtained composite positive electrode material has excellent cycle performance.
[0006] Another object of the present invention is to provide a positive electrode sheet.
[0007] Another object of the present invention is to provide a battery.
[0008] Another object of the present invention is to provide an electrical device.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A composite positive electrode material comprises a core matrix, a first coating layer and a second coating layer, wherein the first coating layer is arranged on the surface of the core matrix in the form of a film coating, and the second coating layer is arranged on the surface of the first coating layer in the form of a dot coating; the core matrix comprises a lithium nickel cobalt manganese oxide material; the first coating layer comprises a disordered phase material; and the second coating layer comprises a nano lithium iron phosphate material.
[0011] In some embodiments, the lithium nickel cobalt manganese oxide material includes LiNi x Co y Mn z, where 0.8≤x≤0.95, 0 <y≤0.15,0.05≤z<0.15。
[0012] In some embodiments, the core matrix is further doped with a metal element M; the metal element M includes at least one of Zr, Y, Sr, Al, W and Ti.
[0013] In some embodiments, the doping amount of the metal element M is 500-5000 ppm.
[0014] In some embodiments, the disordered phase material includes elements Ni, Co and Mn, and in molar percentage, the element Ni is 20% to 30%, the element Co is 60% to 65%, and the element Mn is 5% to 20%.
[0015] In some embodiments, the first coating layer has a thickness of 10 to 50 nm.
[0016] In some embodiments, the mass content of the second coating layer in the composite positive electrode material is less than or equal to 0.5%.
[0017] In some embodiments, in the second coating layer, the diameter of each dot-shaped coating layer is 10-100 nm.
[0018] The method for preparing the composite positive electrode material as described above comprises the following steps:
[0019] A nickel source solution, a cobalt source solution and a manganese source solution are first mixed to obtain a first solution, the first solution is subjected to solid-liquid separation, a solid is obtained and a first drying is performed to obtain a first material; a lithium source and an organic solvent form a first mixed solution, and the first material and an additive are second mixed and subjected to a first heat treatment to obtain a second solution; the second solution is subjected to a second drying, a first roasting, a low-temperature cooling and a grinding treatment to obtain a second material; a second mixed solution formed by an iron source, a phosphorus source and a solvent is mixed with the second material, and then a second heat treatment, a third drying and a second roasting are performed to obtain a composite positive electrode material.
[0020] In some embodiments, the first mixing specifically includes: stirring and mixing the nickel source, water and an organic solvent and then heating to obtain a nickel source solution, and dropwise adding the cobalt source solution and the manganese source solution into the nickel source solution.
[0021] In some embodiments, the first mixed solution further comprises an element M source; the element M source comprises an oxide corresponding to at least one of Zr, Y, Sr, Al, W and Ti.
[0022] In some embodiments, the second mixing specifically includes: dropping the first material into a first mixed solution formed by a lithium source and an organic solvent, and then adding the additive.
[0023] In some embodiments, the additive includes sodium dihydroxysuccinate, and the amount of the additive is 50 to 200 ppm.
[0024] In some embodiments, the temperature of the first heat treatment is 40-80° C., and the rotation speed of the second mixing is 100-300 r / min.
[0025] In some embodiments, the temperature of the first calcination is 600-1000° C., and the time of the first calcination is 6-12 hours.
[0026] In some embodiments, the low temperature cooling temperature is 0-10°C.
[0027] In some embodiments, in the second mixed liquid, the solvent includes water and an organic solvent, the mass ratio of water to the organic solvent is (2-3):(7-8), and the total mass concentration of the iron source and the phosphorus source is 1% to 3%.
[0028] In some embodiments, the temperature of the second heat treatment is 200-300° C., and the time of the second heat treatment is 4-8 hours.
[0029] In some embodiments, the second calcination temperature is 500-900° C., and the second calcination time is 5-10 hours.
[0030] In some embodiments, during the first mixing process, the heating temperature is 100-200° C. and the heating time is 60-120 min.
[0031] In some implementations, during the first mixing process, the rotation speed of the stirring and mixing is 500-1000 r / min.
[0032] In some embodiments, during the first mixing process, the dropping rate of the cobalt source is 2 to 8 mL / min, and the dropping rate of the manganese source is 4 to 16 mL / min.
[0033] In some implementations, the dripping rate of the first material is 10-25 g / min.
[0034] A positive electrode sheet comprises the composite positive electrode material.
[0035] A battery comprises the positive electrode sheet.
[0036] An electrical device comprises the battery.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) In the composite positive electrode material of the present invention, the disordered phase structure of the surface layer of the core matrix material can inhibit particle breakage caused by volume change during charge and discharge, thereby extending the cycle life of the core matrix material; through the double coating of lithium iron phosphate and the disordered phase, the surface structure of the core matrix material is fully protected, which can protect the core matrix material from being corroded by the electrolyte during charged storage, thereby extending the storage life of the core matrix material in a charged state.
[0039] (2) The preparation method of the composite positive electrode material of the present invention obtains a double-coated composite positive electrode material having a first coating layer and a second coating layer through the coordination of various steps. It can inhibit the particle breakage of the high-nickel material caused by volume change during the charge and discharge process, thereby extending the cycle life of the high-nickel material.
[0040] (3) The battery of the present invention has excellent cycle performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is a scanning electron microscope image (SEM) of the second material in Example 1 of the present invention;
[0043] Figure 2 is a transmission electron microscope image (TEM) of the second material in Example 1 of the present invention;
[0044] Figure 3 This is a scanning electron microscope image of the positive electrode material in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0045] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0046] According to one aspect of the present invention, the present invention relates to a composite cathode material, comprising a core matrix, a first coating layer and a second coating layer. The first coating layer is disposed on the surface of the core matrix in a film-like coating form, and the second coating layer is disposed on the surface of the first coating layer in a dot-like coating form; the core matrix comprises a lithium nickel cobalt manganese oxide material; the first coating layer comprises a disordered phase material; the second coating layer comprises a nano lithium iron phosphate material.
[0047] For the composite cathode material of the present invention, the disordered phase structure on the surface layer of the high-nickel material can inhibit the particle breakage caused by volume change during charge and discharge of the high-nickel material, and prolong the cycle life of the high-nickel material; through the double coating of lithium iron phosphate and the disordered phase, sufficient protection is given to the surface layer structure of the high-nickel material, and the high-nickel material can be protected from the erosion of the electrolyte during charge storage, thereby prolonging the storage life of the high-nickel material in the charged state.
[0048] In some embodiments, the lithium nickel cobalt manganese oxide material comprises LiNi x Co y Mn z , where 0.8 ≤ x ≤ 0.95, x is, for example, 0.8, 0.82, 0.85, 0.88, 0.9, 0.95, etc., 0 < y ≤ 0.15, y is, for example, 0.05, 0.08, 0.1, 0.12, 0.15, etc., 0.05 ≤ z < 0.15, z is, for example, 0.05, 0.08, 0.1, 0.15, etc.
[0049] In some embodiments, the core matrix is further doped with a metal element M, and the metal element M comprises at least one of Zr, Y, Sr, Al, W and Ti, such as a combination of Y and Sr, a combination of Sr and Al, a combination of Al, W and Ti, etc. In some embodiments, the doping amount of the metal element M is 500 - 5000 ppm, such as 500 ppm, 800 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, etc., or a range value between any two of them.
[0050] In some embodiments, the disordered phase material comprises elements Ni, Co and Mn. In terms of mole percentage, element Ni is 20% - 30%, such as 20%, 22%, 25%, 28% or 30%, etc., element Co is 60% - 65%, such as 60%, 62%, 65%, etc., and element Mn is 5% - 20%, such as 5%, 8%, 10%, 12%, 15% or 20%, etc. The disordered phase can exert capacity by normally inserting and extracting lithium ions, thus having no influence on the specific capacity of the cathode material.
[0051] In some embodiments, the thickness of the first coating layer is 10 to 50 nm, such as 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm. The present invention uses a first coating layer of appropriate thickness, which is more conducive to suppressing particle breakage caused by volume change of high-nickel materials during charge and discharge, and extending the cycle life of high-nickel materials.
[0052] In some embodiments, the mass content of the second coating layer in the composite positive electrode material is less than or equal to 0.5%, for example 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.5%, etc. The second coating layer of the present invention adopts an appropriate mass content, which is more conducive to working synergistically with the first coating layer to improve the cycle performance of the composite positive electrode material.
[0053] In some embodiments, in the second coating layer, the diameter of each dot-shaped coating layer is 10-100 nm, such as 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 40 nm, 50 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc., which is much smaller than conventional lithium iron phosphate materials.
[0054] In some embodiments, the Fe / P molar ratio of the lithium iron phosphate material is 1.01-1.05, such as 1.01, 1.02, 1.04 or 1.05.
[0055] In some embodiments, compared with the original nickel cobalt manganese oxide main material, the powder resistivity of the composite positive electrode material increases by 2% to 5% after only a layer of disordered phase coating is applied. After further dot-coating of ultra-nano lithium iron phosphate material on the surface of the disordered phase, the powder resistivity increases by 1% to 3%.
[0056] In some embodiments, the lithium ion diffusion coefficient of the composite cathode material is 5×10 -7 ~5×10 -8 .
[0057] In some embodiments, compared with the original nickel cobalt manganese oxide main material, after the composite positive electrode material is prepared into a pole piece, the resistivity of the negative electrode sheet changes to -1% to 1%, and after the negative electrode sheet is further assembled into a battery, the DC internal resistance of the battery changes to -3% to 3%.
[0058] According to another aspect of the present invention, the present invention also relates to a method for preparing the composite positive electrode material as above, comprising the following steps:
[0059] A nickel source solution, a cobalt source solution and a manganese source solution are first mixed to obtain a first solution, the first solution is subjected to solid-liquid separation, a solid is obtained and a first drying is performed to obtain a first material; a lithium source and an organic solvent are formed into a first mixed solution, and the first material and an additive are second mixed and subjected to a first heat treatment to obtain a second solution; the second solution is subjected to a second drying, a first roasting, a low-temperature cooling and a grinding treatment to obtain a second material; a second mixed solution formed by an iron source, a phosphorus source and a solvent is mixed with the second material, and then subjected to a second heat treatment, a third drying and a second roasting to obtain a composite positive electrode material.
[0060] The preparation method of the composite positive electrode material of the present invention obtains a double-coated composite positive electrode material having a first coating layer and a second coating layer through the coordination of various steps, which can inhibit particle breakage of the high-nickel material due to volume change during the charge and discharge process and extend the cycle life of the high-nickel material.
[0061] In some embodiments, the nickel source is a soluble nickel source, including nickel sulfate. The cobalt source is a soluble cobalt source, including cobalt sulfate. The manganese source is a soluble manganese source, including manganese sulfate. The lithium source includes lithium hydroxide, etc. The iron source can be an iron source, such as iron nitrate. The phosphorus source includes ammonium dihydrogen phosphate.
[0062] In some embodiments, the first mixing specifically includes: stirring and mixing the nickel source, water and organic solvent and then heating to obtain a nickel source solution, and dropping the cobalt source solution and the manganese source solution into the nickel source solution; wherein the stirring and mixing speed is 500-1000r / min, such as 500r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, etc.; the heating temperature is 100-200°C, such as 100°C, 120°C, 150°C, 180°C, 200°C, etc., the heating time is 60-120min, such as 60min, 70min, 80min, 90min, 100min, 120min, etc., and the heating adopts an oil bath method. The drop rate of the cobalt source is 2-8mL / min, such as 2mL / min, 4mL / min, 5mL / min, 6mL / min, 8mL / min, etc. The dropping acceleration rate of the manganese source is 4mL / min, 5mL / min, 8mL / min, 10mL / min, 12mL / min, 16mL / min, etc.
[0063] In some embodiments, the first mixed solution further contains an element M source, and the element M source includes an oxide corresponding to at least one of Zr, Y, Sr, Al, W and Ti.
[0064] In some embodiments, the second mixing specifically includes: adding the first material dropwise to the lithium source and the organic solvent to form a first mixed solution, and then adding the additive. In some embodiments, the additive includes sodium dihydroxysuccinate, and the amount of the additive is 50 to 200 ppm, such as 50 ppm, 60 ppm, 100 ppm, 120 ppm, 150 ppm or 200 ppm. Appropriate second mixing conditions are conducive to ensuring the mixing and reaction of the materials.
[0065] In some embodiments, the temperature of the first heat treatment is 40-80°C, for example, 40°C, 45°C, 50°C, 60°C, 65°C, 70°C, 80°C, and the rotation speed of the second mixing is 100-300r / min, for example, 100r / min, 150r / min, 200r / min, 250r / min or 300r / min, etc.
[0066] In some embodiments, the first calcination temperature is 600-1000°C, for example, 600°C, 700°C, 800°C, 900°C, 1000°C, etc.; the first calcination time is 6-12h, for example, 6h, 7h, 8h, 10h or 12h, etc.
[0067] In some embodiments, the low temperature cooling temperature is 0-10°C, such as 0°C, 1°C, 5°C, 6°C, 8°C, 10°C, etc.
[0068] The appropriate first calcination conditions and low-temperature cooling conditions of the present invention can form an appropriate disordered phase coating layer.
[0069] In some embodiments, in the second mixed solution, the solvent includes water and an organic solvent, and the mass ratio of water to the organic solvent is (2-3):(7-8), such as 2:8, 23:7, etc. The total mass concentration of the iron source and the phosphorus source is 1% to 3%, such as 1%, 1.5%, 2%, or 3%.
[0070] In some embodiments, the temperature of the second heat treatment is 200-300° C., such as 200° C., 220° C., 250° C., 260° C., 280° C., 300° C., etc. The time of the second heat treatment is 4-8 hours, such as 4 hours, 5 hours, 7 hours or 8 hours, etc.
[0071] In some embodiments, the second calcination temperature is 500-900°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 800°C, 900°C, etc., and the second calcination time is 5-10h, for example, 5h, 6h, 7h, 8h, 9h or 10h, etc.
[0072] In some embodiments, the dripping rate of the first material is 10-25 g / min, for example, 10 g / min, 15 g / min, 20 g / min, 25 g / min, etc.
[0073] The iron source, phosphorus source and residual lithium on the surface of the second material react to obtain an ultra-nano lithium iron phosphate precursor, which is uniformly generated on the surface of the second material. Through the above-mentioned appropriate second heat treatment and second calcination, a composite positive electrode material with excellent electrochemical performance is obtained.
[0074] According to another aspect of the present invention, the present invention also relates to a positive electrode sheet, comprising the above-mentioned composite positive electrode material.
[0075] The positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer located on at least one side of the positive electrode current collector, wherein the positive electrode material layer contains the above-mentioned composite positive electrode material, a conductive agent and a binder. The mass percentage of the composite positive electrode material, the conductive agent and the binder is 90%-98%: 1%-5%: 1%-5%. The conductive agent is a combination of one or more conductive carbon black, carbon nanotubes, and graphene;
[0076] According to another aspect of the present invention, the present invention also relates to a battery, comprising the above-mentioned positive electrode sheet.
[0077] The battery of the present invention has excellent cycle performance and safety performance.
[0078] In some embodiments, the battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The negative electrode active material in the negative electrode sheet is a mixture of natural graphite and artificial graphite, and the mass percentage of artificial graphite to natural graphite is 60% to 90%: 10% to 40%.
[0079] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the above-mentioned battery. The electric device includes an electric car and the like.
[0080] The following is further explained in conjunction with specific embodiments and comparative examples.
[0081] Example 1
[0082] A method for preparing a composite positive electrode material comprises the following steps:
[0083] (1) Nickel sulfate is uniformly mixed in a mixed solvent of water and dimethyl sulfoxide, wherein the mass ratio of water to dimethyl sulfoxide is 2:8, and the mixture is stirred at a uniform speed of 700 r / min during oil bath heating. Cobalt sulfate and manganese sulfate are dispersed in cyclohexane and ethyl acetate to prepare solutions with a mass concentration of 20%, and then added to the nickel solution at a speed of 4 mL / min and 8 mL / min, respectively, to obtain a first solution; the nickel source, the cobalt source, and the manganese source are added in a molar ratio of nickel, cobalt, and manganese elements of 9:0.5:0.5, the oil bath temperature is 150° C., and the stirring time is 100 min; the first solution is filtered and dried, and then ground to obtain a first material.
[0084] (2) 45.57 g of lithium hydroxide, 200 mg of zirconium oxide, and 100 mg of tungsten oxide were dispersed in dimethyl sulfoxide and heated and stirred in a water bath to obtain a first mixed solution. The water bath temperature was set to 60° C., the rotation speed was 200 r / min, and the mass concentration was 20%. Subsequently, 100 g of the first material was slowly added to the first mixed solution at a speed of 20 g / min, and 10 mg of sodium dihydroxysuccinate was added, and the mixture was heated and stirred in a water bath to obtain a second solution.
[0085] (3) The second solution is spray dried and ground, and then calcined in a muffle furnace, rapidly cooled in a low-temperature box, and ground to obtain a second material (forming a surface disordered phase), wherein the first calcination temperature is 800° C., the first calcination time is 8 hours, and the temperature of the low-temperature box is 5° C.
[0086] (4) Deionized water and an organic solvent are prepared into a mixed solvent in a ratio of 2:8, and 0.4877 g of ferric nitrate and 0.232 g of ammonium dihydrogen phosphate are dispersed in the mixed solvent to prepare a low-concentration second mixed solution with a mass concentration of 2%.
[0087] (5) The second material is evenly dispersed in a low-concentration second mixed solution, the second mixed solution is placed in a three-necked flask, and heated in an oil bath at 250°C with stirring for 6 hours under the condition of inert gas, the iron source and phosphorus source in the second mixed solution react with the residual lithium on the surface of the second material to obtain an ultra-nano lithium iron phosphate precursor, and the ultra-nano lithium iron phosphate precursor is evenly generated on the particle surface of the second material, and then spray-dried, crushed, second calcined and ground, the atmosphere of the second calcination is 90% nitrogen and 10% hydrogen, to obtain a composite positive electrode material.
[0088] Example 2
[0089] A method for preparing a composite positive electrode material, which differs from Example 1 in that:
[0090] In step (2), zirconium oxide and tungsten oxide are not added.
[0091] Example 3
[0092] A method for preparing a composite positive electrode material comprises the following steps:
[0093] (1) Nickel sulfate is uniformly mixed in a mixed solvent of water and dimethyl sulfoxide, wherein the mass ratio of water to dimethyl sulfoxide is 2:8, and the mixture is stirred at a uniform speed of 500 r / min during oil bath heating. Cobalt sulfate and manganese sulfate are dispersed in cyclohexane and ethyl acetate to prepare solutions with a mass concentration of 20%, and then added to the nickel solution at a speed of 8 mL / min and 16 mL / min, respectively, to obtain a first solution; the nickel source, the cobalt source, and the manganese source are added in a molar ratio of nickel, cobalt, and manganese elements of 9:0.5:0.5, the oil bath temperature is 200° C., and the stirring time is 60 min; the first solution is filtered and dried, and then ground to obtain a first material.
[0094] (2) 45.57 g of lithium hydroxide, 200 mg of zirconium oxide, and 100 mg of tungsten oxide were dispersed in dimethyl sulfoxide and heated and stirred in a water bath to obtain a first mixed solution. The water bath temperature was set to 80° C., the rotation speed was 250 r / min, and the mass concentration was 20%. Subsequently, 100 g of the above-mentioned first material was slowly added to the first mixed solution at a speed of 15 g / min, and 10 mg of sodium dihydroxysuccinate was added, and heated and stirred in a water bath to obtain a second solution.
[0095] (3) The second solution is spray dried and ground, and then calcined in a muffle furnace, rapidly cooled in a low-temperature box, and ground to obtain a second material (forming a surface disordered phase), wherein the first calcination temperature is 1000° C., the first calcination time is 6 hours, and the temperature of the low-temperature box is 10° C.
[0096] (4) Deionized water and an organic solvent are prepared into a mixed solvent in a ratio of 2:8, and 0.4877 g of ferric nitrate and 0.232 g of ammonium dihydrogen phosphate are dispersed in the mixed solvent to prepare a low-concentration second mixed solution with a mass concentration of 2%.
[0097] (5) The second material is evenly dispersed in a low-concentration second mixed solution, the second mixed solution is placed in a three-necked flask, and heated in an oil bath at 300°C with stirring for 4 hours under the condition of inert gas, the iron source and phosphorus source in the second mixed solution react with the residual lithium on the surface of the second material to obtain an ultra-nano lithium iron phosphate precursor, and the ultra-nano lithium iron phosphate precursor is evenly generated on the particle surface of the second material, and then spray-dried, crushed, second calcined and ground, the atmosphere of the second calcination is 85% nitrogen and 15% hydrogen, to obtain a composite positive electrode material.
[0098] Example 4
[0099] A method for preparing a composite positive electrode material comprises the following steps:
[0100] (1) Nickel sulfate is uniformly mixed in a mixed solvent of water and dimethyl sulfoxide, wherein the mass ratio of water to dimethyl sulfoxide is 2:8, and the mixture is stirred at a uniform speed of 1000 r / min during oil bath heating. Cobalt sulfate and manganese sulfate are dispersed in cyclohexane and ethyl acetate to prepare solutions with a mass concentration of 20%, and then added to the nickel solution at a speed of 2 mL / min and 4 mL / min, respectively, to obtain a first solution; the nickel source, the cobalt source, and the manganese source are added in a molar ratio of nickel, cobalt, and manganese elements of 9:0.5:0.5, the oil bath temperature is 100° C., and the stirring time is 120 min; the first solution is filtered and dried, and then ground to obtain a first material.
[0101] (2) 45.57 g of lithium hydroxide, 200 mg of zirconium oxide, and 100 mg of tungsten oxide were dispersed in dimethyl sulfoxide and heated and stirred in a water bath to obtain a first mixed solution. The water bath temperature was set to 40° C., the rotation speed was 150 r / min, and the mass concentration was 20%. Subsequently, 100 g of the above-mentioned first material was slowly added to the first mixed solution at a speed of 25 g / min, and 10 mg of sodium dihydroxysuccinate was added, and heated and stirred in a water bath to obtain a second solution.
[0102] (3) The second solution is spray dried and ground, and then calcined in a muffle furnace, rapidly cooled in a low-temperature box, and ground to obtain a second material (forming a surface disordered phase), wherein the first calcination temperature is 600° C., the first calcination time is 12 h, and the temperature of the low-temperature box is 2° C.
[0103] (4) Deionized water and an organic solvent are prepared into a mixed solvent in a ratio of 2:8, and 0.4877 g of ferric nitrate and 0.232 g of ammonium dihydrogen phosphate are dispersed in the mixed solvent to prepare a low-concentration second mixed solution with a mass concentration of 2%.
[0104] (5) The second material is evenly dispersed in a low-concentration second mixed solution, the second mixed solution is placed in a three-necked flask, and heated in an oil bath at 200°C with stirring for 8 hours under the condition of inert gas, the iron source and phosphorus source in the second mixed solution react with the residual lithium on the surface of the second material to obtain an ultra-nano lithium iron phosphate precursor, and the ultra-nano lithium iron phosphate precursor is evenly generated on the particle surface of the second material, and then spray-dried, crushed, second calcined and ground, the atmosphere of the second calcination is 95% nitrogen and 5% hydrogen, to obtain a composite positive electrode material.
[0105] Comparative Example 1
[0106] A method for preparing a composite positive electrode material is provided, wherein the preparation is performed according to steps (1), (2) and (3) of Example 1 to obtain a second material.
[0107] Comparative Example 2
[0108] A method for preparing a composite positive electrode material comprises the following steps:
[0109] Aqueous solutions of cobalt sulfate, manganese sulfate and nickel sulfate are mixed in proportion, wherein the molar ratio of nickel, cobalt and manganese elements is 9:0.5:0.5, and after stirring at room temperature, the mixture is filtered, dried and crushed to obtain a ternary high-nickel material precursor; then 100 g of the precursor and 45.57 g of lithium hydroxide are mixed and ground, calcined at 750° C. for 8 h, cooled at room temperature and ground to obtain powder A.
[0110] Deionized water and an organic solvent are prepared into a mixed solvent in a ratio of 2:8, and 0.4877g of ferric nitrate and 0.232g of ammonium dihydrogen phosphate are dispersed in the mixed solvent to prepare a low-concentration second mixed solution with a mass concentration of 2%. Powder A is uniformly dispersed in the low-concentration second mixed solution, and the second mixed solution is placed in a three-necked flask, heated and stirred in an oil bath at 250°C for 6 hours under the condition of inert gas, and then spray-dried, crushed, second calcined and ground, and the atmosphere of the second calcination is 90% nitrogen and 10% hydrogen to obtain a composite positive electrode material.
[0111] Comparative Example 3
[0112] Aqueous solutions of cobalt sulfate, manganese sulfate and nickel sulfate are mixed in proportion, wherein the molar ratio of nickel, cobalt and manganese elements is 9:0.5:0.5, and after stirring at room temperature, the mixture is filtered, dried and crushed to obtain a ternary high-nickel material precursor; then 100g of the precursor and 45.57g of lithium hydroxide are mixed and ground, calcined at 750°C for 8h, cooled at room temperature and ground to obtain a finished product, which is a conventional high-nickel positive electrode material.
[0113] Experimental example
[0114] 1. Graph Analysis
[0115] The scanning electron microscope (SEM) image of the second material in Example 1 of the present invention is as follows: Figure 1 As shown in Figure 1, the surface wrinkles are caused by the generation of disordered phase. The transmission electron microscope (TEM) image of the second material is shown in Figure 1. Figure 2 As shown, it can be seen that a layer of amorphous structure appears on the surface of the ternary material, indicating that the disordered phase is successfully coated on the surface of the ternary material. Figure 3 As shown, the surface is relatively smooth.
[0116] 2. Battery performance test
[0117] The positive electrode materials obtained in each embodiment and comparative example are prepared into positive electrode sheets according to the ratio of positive electrode material: carbon nanotubes: binder = 95%: 2.5%: 2.5% (mass ratio), and then formed into a soft-pack battery together with the negative electrode sheet. The active materials in the negative electrode sheet are natural graphite and artificial graphite, and the artificial graphite: natural graphite = 75%: 25% (mass ratio).
[0118] The soft pack battery was subjected to cycle test according to the test steps in Table 1 below.
[0119] Table 1 Testing process of soft pack batteries
[0120]
[0121] The high-temperature storage test process steps are as follows: Use the LAND CT2001A battery testing system to perform 1C constant current charging at room temperature, the charging upper limit voltage is 4.25V, and the charging capacity is recorded as C0. Then place the battery in a 55°C constant temperature box for 7 days. After the placement, discharge at 1C constant current at room temperature, the discharge cut-off voltage is 3V, the discharge capacity is recorded as C1, and the capacity retention rate = C1 / C0×100%.
[0122] The cycle performance test results of the batteries of various embodiments and comparative examples are shown in Table 2.
[0123] Table 2 Battery cycle performance test results
[0124]
[0125] From the above, it can be seen that the composite positive electrode material of the present invention, through the double coating of lithium iron phosphate and disordered phase, gives sufficient protection to the surface structure of the core matrix material, and can protect the core matrix material from being corroded by the electrolyte during charged storage, thereby extending the storage life of the core matrix material in the charged state. The capacity retention rate of the battery after 50 cycles at 1C is above 94%, and the capacity retention rate after storage at 55°C for 7 days is above 88.9%.
[0126] The capacity retention rates of the batteries obtained from the positive electrode materials of Comparative Examples 1 to 3 after 50 cycles at 1C and after 7 days of storage at 55°C were both reduced.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite positive electrode material, characterized in that: It comprises a core matrix, a first coating layer and a second coating layer, wherein the first coating layer is arranged on the surface of the core matrix in a film-like coating form, and the second coating layer is arranged on the surface of the first coating layer in a dot-like coating form; The core matrix includes nickel cobalt lithium manganese oxide material; The first coating layer includes a disordered phase material; The second coating layer includes nano lithium iron phosphate material.
2. The composite positive electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (3): (1) The nickel cobalt manganese oxide material includes LiNi x Co y Mn z , where 0.8≤x≤0.95, 0 <y≤0.15,0.05≤z<0.15; (2) The core matrix is further doped with a metal element M, wherein the metal element M includes at least one of Zr, Y, Sr, Al, W and Ti; (3) The core matrix is further doped with a metal element M, and the doping amount of the metal element M is 500 to 5000 ppm.
3. The composite positive electrode material according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) The disordered phase material comprises the elements Ni, Co and Mn, wherein, in molar percentage, the element Ni is 20% to 30%, the element Co is 60% to 65%, and the element Mn is 5% to 20%; (2) The thickness of the first coating layer is 10 to 50 nm.
4. The composite positive electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (2): (1) The mass content of the second coating layer in the composite positive electrode material is less than or equal to 0.5%; (2) In the second coating layer, the diameter of each dot-shaped coating layer is 10 to 100 nm.
5. The method for preparing a composite positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The nickel source solution, the cobalt source solution and the manganese source solution are first mixed to obtain a first solution, the first solution is solid-liquid separated to obtain a solid and first dried to obtain a first material; the lithium source and the organic solvent are formed into a first mixed solution and the first material and the additive are second mixed and first heat treated to obtain a second solution; The second solution is subjected to a second drying, a first roasting, a low temperature cooling and a grinding process to obtain a second material; A second mixed solution formed by an iron source, a phosphorus source and a solvent is mixed with the second material, and then subjected to a second heat treatment, a third drying and a second calcination to obtain a composite positive electrode material.
6. The method for preparing a composite positive electrode material according to claim 5, characterized in that: Contains at least one of the following features (1) to (10): (1) The first mixing specifically comprises: stirring and mixing a nickel source, water and an organic solvent and then heating to obtain a nickel source solution, and dropwise adding the cobalt source solution and the manganese source solution into the nickel source solution; (2) The first mixed solution further comprises an element M source; the element M source comprises an oxide corresponding to at least one of Zr, Y, Sr, Al, W and Ti; (3) the second mixing specifically comprises: dropping the first material into a lithium source and an organic solvent to form a first mixed solution, and then adding the additive; (4) The additive includes sodium dihydroxysuccinate, and the amount of the additive is 50 to 200 ppm; (5) The temperature of the first heat treatment is 40 to 80° C., and the speed of the second mixing is 100 to 300 r / min; (6) The temperature of the first calcination is 600 to 1000° C., and the time of the first calcination is 6 to 12 hours; (7) The temperature of the low temperature cooling is 0 to 10°C; (8) In the second mixed solution, the solvent includes water and an organic solvent, the mass ratio of water to the organic solvent is (2-3):(7-8), and the total mass concentration of the iron source and the phosphorus source is 1% to 3%; (9) The temperature of the second heat treatment is 200 to 300° C., and the time of the second heat treatment is 4 to 8 hours; (10) The temperature of the second calcination is 500-900° C., and the time of the second calcination is 5-10 hours.
7. The method for preparing a composite positive electrode material according to claim 5, characterized in that: Contains at least one of the following features (1) to (4): (1) During the first mixing process, the heating temperature is 100 to 200° C. and the heating time is 60 to 120 min; (2) During the first mixing process, the stirring and mixing speed is 500 to 1000 r / min; (3) During the first mixing process, the cobalt source is added at a rate of 2 to 8 mL / min, and the manganese source is added at a rate of 4 to 16 mL / min; (4) The dripping rate of the first material is 10-25 g / min.
8. A positive electrode sheet, characterized in that: A composite positive electrode material comprising any one of claims 1 to 4.
9. A battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to claim 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.
Citation Information
Patent Citations
Substrate cryogenic cooling device for manufacturing amorphous and nano microcrystalline film
CN101109071A
Ternary anode material of lithium battery with mesoporous core-shell structure coated on surface and preparation method thereof
CN108899545A
Positive electrode active material and preparation method thereof
CN115832234A
Method for coating lithium ion battery positive electrode material with magnesium borate in situ
CN115863557A
Lithium battery capable of improving safety performance and preparation method thereof
CN115881909A
Cited By
Positive electrode material and preparation method thereof, electrochemical device and electronic equipment
CN120674482A
